The Effect of Business Environment and Resource Adequacy on SME Performance - Tyoso, Jaluanto Sunu Punjul; Amalia, Mei Rani; Wardoyo, Dwi Urip (Westscience Press, 2023)
The present quantitative analysis delves into the complex dynamics that effect the performance of Small and Medium Enterprises (SMEs) in Indonesia. Specifically, the study examines the influence of resource adequacy and the business climate. Regression analysis is used in this robust research design study to investigate the links between SME performance and financial resources, human resources, regulatory frameworks, market competition, technical advancements, and economic conditions and technological resources. The results show complex correlations, highlighting the importance of regulatory assistance, economic stability, competitive market responses, and thorough resource management for the success of small and medium-sized enterprises. The research offers concrete insights that will assist policymakers, business practitioners, and the academic community, adding to the continuing conversation on SME development in Indonesia.